Construction of cDNA library of Dalbergia odorifera induced by low temperature stress and screening of low temperature tolerant genes. - Shaocui Li; Xia An; Fayong Li; Yining Chen; Xiaowen Li (PLoS ONE)
To systematically analyze the gene function of Dalbergia odorifera, the seedlings of D. odorifera were treated with low-temperature stress for 6 h. Total RNA was extracted from a mixture of seedling roots, stems, and leaves, and a low-temperature-induced D. odorifera yeast cDNA expression library was constructed. The library volume was 1.032 × 108 CFU, and the PCR (Polymerase Chain Reaction) identification of the library bacterial fluid showed that the amplification was around 1000 bp, with a single randomly distributed band, indicating that the library had been recombinantly inserted into the pYES2 vector. The GO (Gene Ontology) analysis showed that the library genes were mainly involved in metabolic and stress signaling pathways. The KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway enrichment analysis showed that the genes were primarily related to energy and metabolic pathways. Twenty-one genes were screened or obtained at -20°C for low-temperature tolerance. In addition, the organ expression profiles of the candidate genes were analyzed based on RNA-seq data, and the expression profiles of the candidate genes under low-temperature stress were also examined. The construction of the yeast library provides genetic resources for the analysis of the mechanism of low-temperature tolerance of D. odorifera, which is important for comprehending and utilizing the genetic resources of D. odorifera.